Pinpointing mechanisms of a mechanistic treatment: Dissociable roles for overt and covert attentional processes in acute and long-term outcomes following Attention Bias Modification - Price, Rebecca B. (Clin Psychol Sci, 2019)
Biased patterns of attention towards threat are implicated as key mechanisms in anxiety which can be modified through automated intervention (Attention Bias Modification; ABM). Intervention refinement and personalized dissemination efforts are substantially hindered by gaps in understanding the precise attentional components that underlie ABM’s effects on symptoms—particularly with respect to longer-term outcomes. Seventy adults with transdiagnostic anxiety were randomized to receive 8 sessions of active ABM (n=49) or sham training (n=21). Reaction time and eyetracking data, collected at baseline, post-training, and 1-month follow-up, dissociated multiple core attentional processes, spanning overt and covert processes of engagement and disengagement. Self-reported symptoms were collected out to 1-year follow-up. Covert disengagement bias was specifically reduced by ABM, unlike all other indices. Overt disengagement bias at baseline predicted acute post-ABM outcomes, while covert engagement bias was non-specifically predictive of symptom trajectories out to 1-year follow-up. Results suggest unique and dissociable roles for each discrete mechanism.